Pengaruh Teknik Marmet dengan Masase Payudara pada Ibu Nifas Tiga Hari Post Partum Terhadap Kelancaran ASI dan kenaikan BB Bayi - Anita Widiastuti; Siti Arifah; Wiwin Renny Rahmawati (Poltekkes Kemenkes Semarang, 2015)
The purpose of study was to describe the effect of Marmet technique with breast massage of three days post partum to breastfeeding smoothness and gain baby weight. This study uses the Pre-experiment design desigen form of statistical group comparisons (static group comparasion). Result of the study differences Marmet technique and massase breast in breast milk affect the smooth statistically significant test result states where p value of 0.047 closer to the value of α (0.05). The p-value approach α because the process is both interventions at the two treatment groups were equally significant impact on the smooth breastfeeding. While the difference in influencing infant baby weight on the value of α 5%, was obtained p-value of 0.38, thus statistically in this study there was no difference Marmet technique with breast massase in influencing the baby weight. There are different techniques in Marmet with breast massase affect the smooth breastfeeding on postpartum mothers three days post partum with p value 0.047. Based on the results of statistical tests intervention Marmet technique and breast massase conducted in the two treatment groups were equally significant impact on the smooth breastfeeding. There is no difference in Marmet technique with breast massase affect weight gain in infants.